Review of current typhoid fever vaccines, cross-protection against paratyphoid fever, and the European guidelines - Jane N Zuckerman; Christoph Hatz; Anu Kantele (Taylor & Francis Group, 2017)
Introduction: Typhoid and paratyphoid fever remain a global health problem, which - in non-endemic countries - are mainly seen in travelers, particularly in VFRs (visiting friends and relatives), with occasional local outbreaks occurring. A rise in anti-microbial resistance emphasizes the role of preventive measures, especially vaccinations against typhoid and paratyphoid fever for travelers visiting endemic countries. Areas covered: This state-of-the-art review recapitulates the epidemiology and mechanisms of disease of typhoid and paratyphoid fever, depicts the perspective of non-endemic countries and travelers (VFRs), and collectively presents current European recommendations for typhoid fever vaccination. We provide a brief overview of available (and developmental) vaccines in Europe, present current data on cross-protection to S. Paratyphi, and aim to provide a background for typhoid vaccine decision-making in travelers. Expert commentary: European recommendations are not harmonized. Experts must assess vaccination of travelers based on current country-specific recommendations. Travel health practitioners should be aware of the issues surrounding vaccination of travelers and be motivated to increase awareness of typhoid and paratyphoid fever risks.